Perancangan Bioskop Wayang Lakon Jabang Tetuka (The Design of Shadow Puppet Movie Theater of Jabang Tetuka Play) - Aneng Kiswantoro (Institut Seni Indonesia Yogyakarta, 2020)
AbstractThe Design of Shadow Puppet Movie Theater of Jabang Tetuka Play. This paper aimed to discuss the design of Puppet Cinema with the Jabang Tetuka play. It was assumed that by utilizing digital and audio-visual technology, puppet shows are able to compete with other performances. Puppet Cinema Pakeliran with the Jabang Tetuka play was designed based on the concept of presenting a cinema film. This concept prioritizes two things, namely audio and visual. Jabang Tetuka play was taken from the Javanese shadow puppet story. Alma M. Hawkins design method used as the design method of this work. The Hawkins method includes three stages in the design, namely exploration, experimentation, and formation. The result obtained is a puppet show (pakeliran) of puppet cinema with the Jabang Tetuka play. AbstrakTulisan ini membahas perancangan Bioskop Wayang dengan lakon Jabang Tetuka. Diasumsikan dengan memanfaatkan teknologi digital dan audio-visual, pertunjukan wayang mampu bersaing dengan pertunjukan yang lain. Pakeliran Bioskop Wayang dengan lakon Jabang Tetuka dirancang berdasarkan konsep penyajian film bioskop. Konsep ini mengutamakan dua hal yaitu audio dan visual. Lakon Jabang Tetuka diambil dari cerita wayang kulit purwa. Metode perancangan Alma M. Hawkins dipakai sebagai metode perancangan karya ini. Dalam metode Hawkins tercakup tiga tahapan dalam perancangan ialah eksplorasi, eksperimentasi, dan pembentukan. Hasil yang didapat ialah pertunjukan wayang (pakeliran) bioskop wayang dengan lakon Jabang Tetuka.